Does the Frequency of Watching Television Matters on Overweight and Obesity among Reproductive Age Women in Ethiopia? - Mohammed Ahmed; Abdu Seid; Adnan Kemal (Hindawi Limited, 2020)
Background. Studies in developed countries have revealed an association of different magnitudes between watching television and the risk of being overweight and obese among reproductive age women. Even so, there is no evidence of such an association in the context of the Ethiopian population. Hence, the study aimed to assess the association between watching television with overweight and obesity in a nationally representative sample of Ethiopian women. Methods. A cross-sectional study was conducted by using secondary data analysis from 2016 Ethiopia demographic and health survey among women aged from 15 to 49 years. The samples were selected using a two-stage stratified cluster sampling technique. A total of 10,074 women were included in the analysis. The outcome variables were both overweight and obesity, whereas the main exposure variable was the frequency of watching television. Multivariate logistic regression analysis was performed for adjusting potential confounders. Adjusted odds ratio (AOR) with 95% confidence intervals was used to declare a statistically significant association. Results. The study found that watching television at least once a week was significantly associated with both overweight (AOR: 1.79; 95% CI: 1.20-2.73) and obesity (AOR: 3.76; 95% CI: 2.04-6.95). The study also divulged that the odds of overweight were higher among women aged 25-39 years (AOR: 2.17; 95% CI: 1.25-3.77) and 40-49 years (AOR: 2.69; 95% CI: 1.45-5.00), urban residents (AOR: 1.76; 95% CI:1.17-2.65), attended higher education (AOR:2.11; 95% CI: 1.22-3.65), and richest in the wealth index (AOR: 2.83; 95% CI:1.71-4.68). Similarly, the odds of obesity were higher among women aged 25-39 years and 40-49 years, attended higher education, and the richest in wealth index. Conclusions. The results from this study demonstrated that watching television at least once a week is associated with obesity among reproductive age women in Ethiopia. Therefore, a social behavioral change communication campaign needs to be taken to improve awareness regarding the harmful consequences of watching television for long hours. Further research studies should be conducted among men and adolescents to determine whether this positive association exists among that target population as well.